Live Imaging of Influenza Infection of the Trachea Reveals Dynamic Regulation of CD8+ T Cell Motility by Antigen. - Kris Lambert Emo; Young-Min Hyun; Emma Reilly; Christopher Barilla; Scott Gerber; Deborah Fowell; Minsoo Kim; David J Topham (PLoS Pathogens, 2016)
During a primary influenza infection, cytotoxic CD8+ T cells need to infiltrate the infected airways and engage virus-infected epithelial cells. The factors that regulate T cell motility in the infected airway tissue are not well known. To more precisely study T cell infiltration of the airways, we developed an experimental model system using the trachea as a site where live imaging can be performed. CD8+ T cell motility was dynamic with marked changes in motility on different days of the infection. In particular, significant changes in average cell velocity and confinement were evident on days 8-10 during which the T cells abruptly but transiently increase velocity on day 9. Experiments to distinguish whether infection itself or antigen affect motility revealed that it is antigen, not active infection per se that likely affects these changes as blockade of peptide/MHC resulted in increased velocity. These observations demonstrate that influenza tracheitis provides a robust experimental foundation to study molecular regulation of T cell motility during acute virus infection.